Validity of Digital Comics to Train Metacognitive Skills on Thermochemical Materials - Hasna Choiriyah; Rusly Hidayah (Universitas Pendidikan Mandalika, 2023)
The purpose of this study was to determine the validity of digital comics to train students' metacognitive skills on thermochemical material seen from content and construct validation. The novelty of this research is to develop digital comics that have metacognitive components. The research subjects were high school students grade XI. The data used in the pre-research was from 30 students of class XI from one of the state high schools in Magetan. This research uses research and development (R&D) procedures with the ADDIE method, namely analyze, design, develop, implement, and evaluate. But only up to the development stage to find out the validation of digital comics. The instruments used in this study used digital comic review sheets filled in by reviewers and digital comic validation sheets filled in by experts, namely two chemistry lecturers and one chemistry teacher. Based on the results of validation by experts, it shows that the digital comics developed obtained mode 4 for content validation with a valid category, and obtained mode 4 for construct validation to obtain a valid category. Based on the validation results, the developed digital comics can be said to be valid for use as learning media to train students' metacognitive skills.